Analisis Pengaruh Islamic Corporate Governance Terhadap Corporate Social Responsibility (Studi kasus pada Bank Syariah di Indonesia) - Haribowo, Ismawati (Faculty of Economic and Business, 2015)
This study aims to examine the influence of Islamic corporate governance, size of the Board of Commissioners, the composition of the Board of Commissioners, Frequency of Meetings of the Board of Commissioners, the size of the Audit Committee Independent, The composition of the Audit Committee Number of Meetings Audit Committee, Profitability and Liquidity on the disclosure of corporate social responsibility (case study on the bank Sharia in Indonesia). This research is a quantitative study using scientific research in the form of positive economics. The nature and type of this research is descriptive method used is based on a survey of the literature. Data used is secondary data obtained from www.bi.go.id and corporate websites. The analytical method used is multiple linear regression analysis with SPSS version 22. The population in this study are all Islamic banks registered in Bank Indonesia during the period 2012 to 2014. While the sample is determined by using purposive sampling method in order to obtain a sample of 10 banks with observations for 3 years.Based on the results of multiple regression analysis with significance level of 5%, then the results of this study concluded: (1) Islamic Corporate Governance consisting of Existence and expertise Sharia Supervisory Board has no significant effect on the disclosure of corporate social responsibility. (2) The size of the BOC significant effect on the disclosure of corporate social responsibility. (3) The composition of the Board of Commissioners has no significant effect on the disclosure of corporate social responsibility. (4) The frequency of the number of board meetings no significant effect on the disclosure of disclosure of corporate social responsibility. (5) The size independent audit committee has no significant effect on the disclosure of corporate social responsibility. (6) The composition of the independent audit committee has no significant effect on the disclosure of corporate social responsibility. (7) The number of meetings of the audit committee has no significant effect on the disclosure of corporate social responsibility. (8) Profitability has no significant effect on the disclosure of corporate social responsibility. (9) Liquidity no significant effect on the disclosure of corporate social responsibility. (10) Islamic corporate governance, size of the Board of Commissioners, the composition of the Board of Commissioners, Frequency of Meetings of the Board of Commissioners, the size of the Audit Committee Independent, The composition of the Audit Committee Number of Meetings Audit Committee, Profitability and Liquidity on the disclosure of corporate social responsibility jointly significant effect on disclosures corporate social responsibility.DOI: 10.15408/ess.v5i1.2338